Islam dan Ilmu Pengetahuan: Integrasi Ontologis, Epistemologis, dan Aksiologis Kontemporer - Sukmawati Markun; Ramsiah Tasruddin (Advances In Education Journal, 2025)
This article examines the integration of Islam and science from the perspectives of the Qur’an and contemporary thought by employing the framework of Islamic philosophy of science. The study demonstrates that, in Islam, knowledge is not understood merely as a rational–empirical activity, but as a reality rooted in the principle of tawḥīd and ultimately derived from Allah. Ontologically, Islam conceives reality as encompassing both physical and metaphysical dimensions, both of which constitute legitimate objects of knowledge. Epistemologically, Islam integrates revelation, reason, sensory perception, and the heart as complementary sources of knowledge within a hierarchical and integrative system. Axiologically, knowledge in Islam is not value neutral; rather, it is oriented toward public welfare, justice, and the strengthening of faith. This article also explores the classical Islamic scientific tradition as well as contemporary discourses on the Islamization of knowledge and the integration of Islam and science as critical responses to the dominance of secular modern scientific paradigms. Accordingly, this study affirms that the integration of Islam and science offers a holistic, ethical, and meaningful paradigm of knowledge that is highly relevant to the challenges of contemporary civilization.